2009
DOI: 10.1536/ihj.50.153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atorvastatin and Simvastatin in Prevention of Atrial Fibrillation After Successful Cardioversion

Abstract: SummaryRecent data have shown that statins can help prevent atrial fibrillation (AF). We hypothesized that statins vary in their ability to prevent AF after successful electrical cardioversion (EC).Sixty-five patients (29 receiving atorvastatin and 36 receiving simvastatin) who had undergone successful EC for persistent AF were included in the study. They received statins at least one month before EC, and continued the treatment through 2 years of followup. The statins they received were selected independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…43) In addition, Naji, et al reported that atorvastatin was superior to simvastatin for preventing recurrence of persistent AF after electrical cardioversion in their retrospective study. 45) Our results were similar to those of Naji, et al showing atorvastatin to be more effective in preventing recurrence of paroxysmal AF than pravastatin. These results suggest that different types of statin treatments exert different levels of efficacy in preventing recurrence of paroxysmal AF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…43) In addition, Naji, et al reported that atorvastatin was superior to simvastatin for preventing recurrence of persistent AF after electrical cardioversion in their retrospective study. 45) Our results were similar to those of Naji, et al showing atorvastatin to be more effective in preventing recurrence of paroxysmal AF than pravastatin. These results suggest that different types of statin treatments exert different levels of efficacy in preventing recurrence of paroxysmal AF.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, few studies have examined the efficacy of statins in patients with paroxysmal 44) and persistent AF on a long-term basis (> 2 years). 41,45) Pravastatin, a hydrophilic statin, was considered to be effective for preventing recurrence of AF after electrical cardioversion in a retrospective study, whereas its efficacy was neglected in a randomized open-label multicenter study. 42) However, atorvastatin, a lipophilic statin, was demonstrated to be effective for preventing recurrence of paroxysmal and persistent AF in a prospective randomized study.…”
Section: Discussionmentioning
confidence: 99%
“…Six trials examined patients with coronary artery disease [18,19,[21][22][23][24][25], six trials examined effect of statins in patients undergoing electrical conversion [26][27][28][29][30][31], four trials were on patients with MI [32][33][34][35], and four trials were undertaken in patients with pacemaker or implantable cardioverter-defibrillator (ICD) [36][37][38][39]. Two trials analyzed primary prevention of AF [17,40], one trial was on patients with heart failure [20], one trial was on AF after cerebral infarction, [41] one trial investigated in elderly patients [32] and finally one trial examined patients with left ventricular hypertrophy [42].…”
Section: Characteristics Of the Studies And Patientsmentioning
confidence: 99%
“…As it might be expected there was no significant effect among these studies. It has been suggested that different statins exert different preventive effect on AF [26]. When analyzing the effect of statins individually, in RCTs, no beneficial effect was noticed.…”
Section: Effect According To Classification Of Atrial Fibrillationmentioning
confidence: 99%
“…Nevertheless, an increase of gap junctional conductance by some compounds or methods can protect heart from life-threatening arrhythmia (Greener et al, 2012). Non-antiarrhythmic drugs simvastatin, coming as a surprise, exhibit antiarrhythmic ability in human by some unclear mechanism (Naji et al, 2009;Van Gelder, 2007). Moreover, beyond to its classical cholesterol-lowering action, simvastatin exerts benificial effects on osteoporosis, inflammation and other diseases that connexins also play a part in (Uzzan et al, 2007;van der Meij et al, 2013).…”
Section: Discussionmentioning
confidence: 99%